Drawing on Trouillot's concept of the savage slot to analyze the rehashed imaginaries of Latin American indigeneities. Issue 1 (2nd January 2023) - Balán, Laura
ABSTRACT: The world order that germinated with the colonial encounter of Christianity with indigenous peoples from the 'new continent' created the ideological construct of 'the West.' The purpose of this work is to show that there is coherence and continuity between the world order that started at the end of the 15th century and contemporary processes such as ideological mestizaje in Latin America, identity politics, transnational political identities, and the flourishing of Indian hobbyist groups in several European countries. To this end, I will deploy Michel-Rolph Trouillot's notion of the savage slot – an ideological construct through which 'the West' organizes the world and thinks about itself. Moreover, I will put Trouillot approach in dialogue with the contributions of other contemporary authors to understand the specific social and ideological dynamics involved in the representation of indigenous peoples in Latin America, particularly in Colombia.